ANALISIS TINGKAT PARTISIPASI ANGGOTA KOPERASI SERBA USAHA PETERNAK MOTIVASI DO’A IKHTIAR TAWAKKAL (KSUP MDIT) DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Fikri Syahputra; Septi Monica Sari; Ainul Mardliyah (Jurnal WACANA PERTANIAN, 2019)
This study aims to analyze the level of participation of cooperative members in RAT, pay deposits, and utilize existing business services in cooperatives, analyzing the influence of member participation on the economic benefits of cooperatives received by cooperative members. This research was conducted by descriptive method. The study sample was 55 people who as a whole were members of the all-round cooperative business of MDIT farmers. The data collected consists of primary data and secondary data. The analytical method used is the level of participation analysis and multiple linear regression analysis. The results showed that the level of participation of members in RAT and paying deposits must be included in the high category while participation in the utilization of business units is included in the low category. Based on the results of multiple linear regression analysis, it is known that the participation of cooperative members has no significant effect on the magnitude of the economic benefits of cooperatives received by members in the past year.